Women in farmer–herder conflicts: case studies from Sudan and Nigeria - Nassef, Magda; Sulieman, Hussein; Momale, Saleh; Higazi, Adam; Domingo, Pilar (SPARC Knowledge, 2025)
Women are seldom mentioned in studies on farmer–herder conflict. When they do feature, they are predominantly portrayed as victims of conflict rather than actors exercising agency. Although recent literature on women and conflict has begun to consider voice and agency, this is less evident within farmer–herder conflict or the broader land and conflict nexus. This SPARC research addresses this gap, using qualitative case studies in Sudan and Nigeria. In Sudan, the research examines conflicts between farmers (mixed ethnic groups) and Fallata pastoralists in Azaza Sogora village in Gadarif State. In Nigeria, the research examines conflicts between Fulani pastoralists and Tiv and Hausa farmers in Jangargari village in Awe Local Government, Nasarawa State. Focus group discussions (FGDs) and key informant interviews (KIIs) highlight distinct dynamics of farmer–herder conflicts and their impacts, which are shaped by local contexts that interact with state policies, environmental conditions, wider insecurity, and other factors. While both areas face challenges related to resource competition and gender inequalities, the intensity of conflict and the roles of women in livelihoods and conflict differ significantly.